2019
DOI: 10.3390/ijms20163931
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysed Collagen from Sheepskins as a Source of Functional Peptides with Antioxidant Activity

Abstract: The extraction and enzymatic hydrolysis of collagen from sheepskins at different times of hydrolysis (0, 10, 15, 20, 30 min, 1, 2, 3 and 4 h) were investigated in terms of amino acid content (hydroxyproline), isoelectric point, molecular weight (Mw) by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) method, viscosity, Fourier-transform infrared (FTIR) spectroscopy, antioxidant capacity by 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 73 publications
(88 reference statements)
3
43
0
Order By: Relevance
“…Amide II (1548 cm −1 ) and Amide III (1248 cm −1 ) were mainly associated with intermolecular interactions, representing the stretching vibrations of the CN group and the deformation of the NH group of the amide bonds, respectively. These peaks were observed in a previous work where HC was extracted [ 23 ]. The increase in the amplitude in the region of 3000 to 3500 cm −1 was also attributed to hydrogen bonds, due to the presence of the molecular chains interacting by inter- and intra-molecular hydrogen bonds [ 56 ].…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Amide II (1548 cm −1 ) and Amide III (1248 cm −1 ) were mainly associated with intermolecular interactions, representing the stretching vibrations of the CN group and the deformation of the NH group of the amide bonds, respectively. These peaks were observed in a previous work where HC was extracted [ 23 ]. The increase in the amplitude in the region of 3000 to 3500 cm −1 was also attributed to hydrogen bonds, due to the presence of the molecular chains interacting by inter- and intra-molecular hydrogen bonds [ 56 ].…”
Section: Resultssupporting
confidence: 64%
“…HC was obtained according to a previously determined methodology [ 23 ]. Native collagen was suspended in 1 M NaCO 3 at a ratio of 1:4 ( w/v ).…”
Section: Methodsmentioning
confidence: 99%
“…The smaller the peptides, more pores will be formed and increase the open structure in the image. León-López et al [42] found out that SEM images of the hydrolyzed collagen from sheepskin had a porous and spongy structure, which the degradation of the protein can be seen upon increasing the hydrolysis time.…”
Section: Scanning Electron Microscpymentioning
confidence: 99%
“…They found that the antioxidant properties of HC depended on the size of the molecules; the lower the molecular weight of peptides, the greater the ability to donate an electron or hydrogen to stabilize radicals. The best treatment was observed when HC was obtained after four hours of enzymatic hydrolysis with an average molecular weight of 5 kDa [81].…”
Section: Role Of Hydrolyzed Collagen As An Antioxidant Ingredientmentioning
confidence: 99%